Continuities in the HIV/AIDS Policy Debate in South Africa: An Observational Approach - Lincoln J. Fry (Issues and Development in Health Research Vol. 6, 2021)
This is an issue to be addressed in this paper’s analysis section where the prioritization of HIV/AIDS and Health by South Africans are compared. Utilizing the South African sample from the Fourth Round of the Afrobarometer survey, this paper identifies the factors which predicted respondent selection of HIV/AIDS as an important issue for the government to address. The identification of HIV/AIDS as an important governmental problem became the study’s dependent variable. Other possible important factors were whether respondents had personal knowledge of HIV/AIDS, meaning they knew someone who died of AIDS, poverty, and their assessments of the way the government was handling the HIV/AIDS crisis. Respondent background and demographic characteristics were also included in a logistic regression analysis. The results identified three factors that predicted respondent choice of HIV/AIDS: race, especially being a Black South African, the choice of health as a governmental priority, and the rural-urban dimension. The conclusion was that HIV/AIDS, as opposed to health, should be the focus of campaigns designed to mobilize public support of comprehensive HIV/AIDS strategies in South Africa.